تقييم مدى تطبيق المنهج العلمي المتكامل في إدارة الأزمات في المنظمات الصناعية السورية (دراسة حالة المؤسسة العامة للتبغ –فرع المنطقة الساحلية) - سليطين سوما (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The research deals the complete scientific method of The crisis management and the importance of its application, and aims to know the differences between it and the followed method of The crisis management in one of the Syrian Industrial Organizations,it is the general corporate of tobacco -coastal region branch) The research relied the analysis descriptive approach as a general method The most important results of the research have been represented as follows : The big and positive difference between followed method of The crisis management in the organization under study and the complete scientific method of The crisis management. The most important recommendations the following:- The general corporate of tobacco -coast region branch must have the early warning systems which Can help to define the gestures that can predict the capability of crisis that may happen. -The corporate must keep its own file about crises which passed on, and its useful lesson. تناول هذا البحث المنهج العلمي المتكامل في إدارة الأزمات بجميع مراحله,وأهمية تطبيقه, وهدف إلى معرفة الفروق بينه وبين المنهج المتبع في إدارة أزمات إحدى المنظمات الصناعية السورية, وهي المؤسسة العامة للتبغ (فرع المنطقة الساحلية), وقد تم الاعتماد على المنهج الوصفي التحليلي كمنهج عام للبحث. وقد تمثلت أهم نتائج البحث بالآتي: وجود فروق جوهرية إيجابية بين المنهج المتبع في إدارة أزمات المؤسسة محل البحث وبين المنهج العلمي المتكامل في إدارة الأزمات . وتمثلت أهم توصيات البحث بالآتي: 1-يجب أن تسعى المؤسسة العامة للتبغ(فرع المنطقة الساحلية) لامتلاك نظم إنذار مبكرة تساعدها في تحديد المؤشرات التي تنبئ بإمكانية حدوث الأزمات. 2-يجب أن تحتفظ المؤسسة المبحوثة بسجل خاص بها عن الأزمات التي تمر بها والدروس المستفادة منها.